(untitled) (Research, Society and Development, 2021)
Fracture of an endodontic instrument within the root canal system can occur due to incorrect use of instruments, and clinicians are confronted with a few removal options when considering this situation. The purpose of this article is to present the removal of a fractured endodontic file from the periapical region of the right upper central incisor, that caused a nasal floor perforation and otorhinolaryngological symptoms, with the aid of a dental operating microscope (DOM) and cone bean computed tomography (CBCT). Success was achieved when the fragment was visible and removed from the nasal fossa. The standardized techniques of removal or bypassing fracture file were not effective, and success was obtained with the aid of CBCT that made possible the visualization of the broken file inside the nasal fossa.